KAJIAN SEMIOTIK PADA KUMPULAN CERPEN SEKUNTUM MAWAR DI DEPAN PINTU KARYA M. ARMAN A.Z. - Diana, Ani (JURNAL PESONA, 2016)
Literary works are human beings art works which giving aesthetic athmosphere forhim. It becomes a medium for literary men in delivering their ideas and messagesabout humansâ life. There are some of literary works and one of them is short story. Ashort story is a literary work which telling story about a character in short, which canbe red in a time since only tell single situation. It tells humansâ problems in physicaland mental side, which create a conflict which is delivered inform of semiotics whichhave their own meanings.Keywords: icon, index, and symbol